2023
DOI: 10.1101/2023.02.09.527809
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nicotinic acetylcholine receptor signaling maintains epithelial barrier integrity

Abstract: Disruption of epithelial barriers is a common disease manifestation in chronic degenerative diseases of the airways, lung and intestine. Extensive human genetic studies have identified risk loci in such diseases, including in chronic obstructive pulmonary disease (COPD) and inflammatory bowel diseases (IBD). The genes associated with these loci have not fully been determined, and functional characterization of such genes requires extensive studies in model organisms. Here, we report the results of a screen in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…Acetylcholine is well known as a primary neurotransmitter in the central nervous system, but reports have also shown that peripheral acetylcholine plays an important role including in regulation of immunity [33] and gut barrier homeostasis [34]. Since acetylcholine promotes gut motility in mammals [35] and potentially in Drosophila [16], we hypothesized that acetylcholine mediates the effect of L.p culture supernatant on GI motility.…”
Section: Resultsmentioning
confidence: 99%
“…Acetylcholine is well known as a primary neurotransmitter in the central nervous system, but reports have also shown that peripheral acetylcholine plays an important role including in regulation of immunity [33] and gut barrier homeostasis [34]. Since acetylcholine promotes gut motility in mammals [35] and potentially in Drosophila [16], we hypothesized that acetylcholine mediates the effect of L.p culture supernatant on GI motility.…”
Section: Resultsmentioning
confidence: 99%